Secrets in summer : a novel - Thayer, Nancy, 1943- (Ballantine Books, 2017)
"Darcy Cotterill, 30 and divorced, works at the Nantucket library during the day. She spends most nights in her backyard, gazing at the stars. She's on the brink of starting a relationship with a local carpenter, Nash, when she gets new neighbors for the summer, the most unexpected of whom are her ex-husband, his new wife, and step-daughter. As Darcy is drawn into the lives of her neighbors, she develops a crush on another vacationer, Clive, a musicologist visiting with his grandmother. Over the course of the summer, Darcy is driven to decide what she truly wants--is she over her ex? Will she choose Nash or Clive?"--